Mid upper-arm circumference is an effective tool to identify infants and young children with severe acute malnutrition in India. Issue 17 (11th March 2015) - Aguayo, Victor M; Aneja, Satinder; Badgaiyan, Nina; Singh, Karanveer
Abstract: Objective: To assess the appropriateness of current mid upper-arm circumference (MUAC) cut-offs to identify children with severe acute malnutrition in India. Design: The analysis concerned 6307 children admitted to nutrition rehabilitation centres (2009–2011) where they received therapeutic care as per guidelines by WHO and the Indian Academy of Pediatrics. Setting: States of Jharkhand, Madhya Pradesh and Uttar Pradesh, India. Subjects: Children aged 6–59 months with bilateral pitting oedema or weight-for-height Z -score (WHZ)<−3 or MUAC<115 mm at admission. Results: Children aged 6–23 months represented ~80 % of the admissions. Among them, the proportion with WHZ<−3 was similar to that with MUAC<115 mm (85·7 % v. 81·8 %); the proportion with MUAC<115 mm whose WHZ was <−3 was 82·6 %; and the proportion with WHZ<−3 whose MUAC<115 mm was 78·8 %. MUAC<115 mm was as effective as WHZ<−3 in identifying 6–59-month-old children with medical complications (32·2 % v. 31·6 %, respectively), the most important risk factor of death among oedema-free children. Furthermore, death rates in children with MUAC<115 mm were higher than in children with WHZ<−3 (0·61 % v . 0·58 %, respectively) and 91 % of the deaths among oedema-free children were deaths of children with MUAC<115 mm. Conclusions: In populations similar to those included in our analysis, MUAC<115 mm appears to be an appropriate criterion to identify children with severe acute malnutrition who are at a greater risk of medical complications and death, particularly among children 6–23 months old.